Do operating models of SMMEs contribute to economic stimulation and growth? A review of the literature - Mahosi, Brian Ngwako; Sibiya, Ayanda (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to explore the effectiveness of operating models for SMMEs in the context of economic stimulation and growth. As the development of SMMEs is essential for their sustainability and expansion, enhancing and refining their operating models becomes crucial. Such improvements can lead to more efficient and profitable businesses that can thrive in the mainstream economy. Methodology: By evaluating the effectiveness of these models, this research addresses existing gaps in the literature concerning their impact on SMMEs. To investigate the effectiveness of operating models for SMMEs, a comprehensive literature review was conducted. Findings: The study reveals that SMMEs make significant contributions to the South African economy by operating in neglected markets, serving local communities, and stimulating economic growth. By adopting effective operating models, SMMEs can optimize resource utilization, improve efficiency, and make informed decisions. Furthermore, integrating principles of quality, ethical practices, and environmental sustainability within the operating model enables SMMEs to build trust, preserve natural resources, and enhance resilience. In conclusion, by recognizing the importance of operating models and taking concerted efforts to develop and implement them, countries can empower SMMEs to fulfil their potential as drivers of economic development and social progress in the country. Originality/value: This paper is original Paper type: a Research Paper